CARDIOLOGY NURSE: FUNCTIONS, COMPETENCES AND ROLE IN IMPROVING TREATMENT OUTCOMES (International journal of medical sciences, 2025)
This article examines the important role of the nurse in cardiovascular disease, focusing on key tasks and functions, including patient monitoring, preventive measures, education, emotional support, and documentation. Key aspects that help improve patient care and contribute to increased treatment effectiveness are outlined. It demonstrates how nursing supports a comprehensive approach to treatment and rehabilitation, making it an integral part of the modern healthcare system.